The relationship between histopathological subtypes and recurrence in basal cell carcinoma patients: A case-control study - Rahmat, Beatta Meidini; Sahudi, Sahudi; Wibowo, Marjono Dwi (Edelweiss Applied Science and Technology, 2025)
Basal cell carcinoma is an epithelial malignancy characterized by indolent growth and a rare tendency to metastasize, but it can cause significant soft tissue damage. Worldwide, basal cell carcinoma is the most commonly diagnosed type of skin cancer, accounting for approximately 25% of all skin cancers due to the aging population and increased exposure to sunlight. Recurrence of basal cell carcinoma after complete surgical excision is rarely reported, and risk factors are not well studied. Histopathological subtype is an important factor in determining excision margins and further management, as it provides predictive information regarding tumor behavior and the risk of recurrence. This study aims to determine the relationship between histopathological subtypes and the incidence of recurrence in basal cell carcinoma patients at Dr. Soetomo General Hospital Surabaya for the period from January 2017 to December 2023. All patients between January 2017 and December 2023 whose primary BCCs were excised with free surgical margins according to histopathology reports were included, and a case-control study was conducted using medical files to record patients' age, sex, tumor site, size, histopathology variant, and recurrence. Based on the chi-square odds ratio calculation, the high-risk subtype increased the chance of recurrence by 13 times (OR 3.9-42.9) compared to the low-risk subtype. There was no significant relationship between recurrence and the patient's sex, age, or tumor site. There is a relationship between histopathological subtypes and recurrence in basal cell carcinoma at Dr. Soetomo General Hospital Surabaya for the period from January 2017 to December 2023.